Hand knitting induced thrombosis of the subclavian vein in a young woman: an unusual cause of Paget-Schoetter Syndrome - Aytekin Alcelik; Haluk Savli; Ahsen Zeyrek; Abdullah Yalcin (Mediterranean Journal of Hematology and Infectious Diseases)
Effort thrombosis refers to axillary-subclavian vein thrombosis associated with strenuous and repetitive activity of the upper extremities. Effort thrombosis usually follows sporting activities, such as wrestling, playing ball, gymnastics and swimming, which involve vigorous andnsustained upper extremity movements. Heretofore, We report a case of Paget-Schroetter syndrome characterized by hand knitting triggered thrombosis of the subclavian vein.